Efficacy of active forced air warming during induction of anesthesia to prevent inadvertent perioperative hypothermia in intraoperative warming patients: Comparison with passive warming, a randomized controlled trial. Issue 12 (26th March 2021) - Yoo, Jae Hwa; Ok, Si Young; Kim, Sang Ho; Chung, Ji Won; Park, Sun Young; Kim, Mun Gyu; Cho, Ho Bum; Song, Sang Hoon; Cho, Chae Yeon; Oh, Hong Chul
Abstract: Background: This study aimed to evaluate the efficacy of peri-induction forced air warming to prevent inadvertent perioperative hypothermia, defined as a reduction in body temperature to <36.0°C during the perioperative period, in intraoperatively warmed patients receiving major surgery lasting >120 minutes. Methods: In total, 130 patients scheduled for elective surgery under general anesthesia lasting >120 minutes were divided into 2 groups: peri-induction warming (n = 65) and control (n = 65). Patients in the peri-induction warming group were warmed during the anesthetic induction period using a forced-air warmer set at 47°C, whereas patients in the control group were covered passively with a cotton blanket. All patients were warmed with a forced-air warmer during surgery. Body temperature was measured using a tympanic membrane thermometer in the pre- and postoperative periods and using a nasopharyngeal temperature probe during surgery. Patients were evaluated for shivering scale score, thermal comfort scale score, and satisfaction score in the post-anesthesia care unit. Results: The incidence rates of intraoperative and postoperative hypothermia were lower in the peri-induction warming group than in the control group (19.0% vs 57.1%, P  < .001; 3.3% vs 16.9%, P  = .013, respectively). Body temperature was higher in the peri-induction warming group ( P  < .001). However, intraoperative blood loss, as well as postoperative thermal comfort scale score, shivering scale score, and patient satisfaction score, were similar between groups. Post-anesthesia care unit duration was also similar between groups. Conclusions: Peri-induction active forced air warming is an effective, simple, and convenient method to prevent inadvertent perioperative hypothermia in intraoperatively warmed patients undergoing major surgery lasting >120 minutes.